How do the Banking Systems of High Income Countries differ from others? - Halil D. Kaya (Financial Markets, Institutions and Risks)
In this study, first we look at the relation between countries’ income levels and their banking systems. What are the differences between richer countries and other countries in terms of their banking systems? Then, we look at how OECD membership affects the banking system of a country. When we compare High-Income countries to Middle- and Low-Income countries, we find that workers’ remittances are much higher in Low- and Middle-income countries. The banking industries are much more concentrated in High-Income countries. Bank deposits are also significantly higher in these countries. The banking systems in these countries have more risk compared to their counterparts in other countries. Non-resident banks are more active in High-Income countries. Also, there is more interest in offshore accounts and the banks are more engaged in international transactions. When we compare high-income OECD-member countries to high-income Non-OECD-member countries, we find that the banking industries in high-income Non-OECD-member countries are much more concentrated when compared to their counterparts in High-Income OECD countries. In High-Income Non-OECD countries, non-resident banks are more active and there is more interest in offshore accounts. On the other hand, bank deposits are higher in High-Income OECD countries. But, the banks in these countries are in greater risk compared to the banks in Non-OECD countries (i.e. liquid liabilities are higher). We conclude that policymakers need to consider OECD membership and income level as determinants of a country’s banking system.